Real‐World Effectiveness of Obeticholic Acid in Patients with Primary Biliary Cholangitis. Issue 9 (6th July 2020) - Roberts, Surain B.; Ismail, Marwa; Kanagalingam, Gowthami; Mason, Andrew L.; Swain, Mark G.; Vincent, Catherine; Yoshida, Eric M.; Tsien, Cynthia; Flemming, Jennifer A.; Janssen, Harry L.A.; Hirschfield, Gideon M.; Hansen, Bettina E.; et al.
Abstract : Patients with primary biliary cholangitis (PBC) with incomplete response to ursodeoxycholic acid are at risk of disease progression and need additional therapy. Obeticholic acid (OCA) was approved in Canada in May 2017, but its effectiveness in a real‐world setting has not been described. We sought to describe our experience with OCA in a Canadian cohort. OCA‐naive patients treated at two Canadian centers were included. Clinical and biochemical data were collected at OCA initiation and during follow‐up. Primary outcomes were changes in serum alkaline phosphatase (ALP), gamma‐glutamyl transferase (GGT), and total bilirubin (TB) over the duration of therapy. Secondary outcomes were changes in alanine aminotransferase (ALT), aspartate aminotransferase (AST), immunoglobulin M (IgM), platelets, and albumin; and achievement of the primary endpoint of the original phase 3 study that led to OCA approval (A Placebo‐Controlled Trial of Obeticholic Acid in Primary Biliary Cholangitis [POISE]), dose reductions, discontinuations, and tolerability. Repeated‐measures models were used to assess changes in biochemistry over time. Sixty‐four patients were included; 4 carried a diagnosis of overlap with autoimmune hepatitis. Mean age was 54.6 years, median ALP was 250 U/L, TB was 13 µmol/L, platelet count was 225 × 10 9 /L, and 24% had liver stiffness measurements ≥16.9 kPa. There was a significant reduction in mean ALP of 55 U/L ( P < 0.001), GGT of 138 U/L ( P < 0.001), ALT of 11.9 U/L ( P < 0.001), AST of 5.7 U/L ( P < 0.05), and IgM of 0.70 g/L ( P < 0.001) over 12 months; TB remained stable ( P = 0.98). Forty‐four patients met POISE‐inclusion criteria, 39% (n = 17) of whom had 12‐month biochemical measurements. In this subset, 18% (n = 3/17) met the 12‐month POISE primary endpoint, but considering follow‐up to 19 months, 43% achieved this target (n = 9/21). Pruritus was the most commonly reported complaint. Conclusion : Use of OCA was associated with improvement in biochemical surrogates of outcome in PBC in a real‐world setting. Abstract : Patients with Primary Biliary Cholangitis with incomplete response to ursodeoxycholic acid are at risk of disease progression and need additional therapy. Obeticholic acid (OCA) was approved for use in Canada in May 2017, but its effectiveness in a real‐world setting has not been described. Herein we demonstrate that use of OCA was associated with improvement in biochemical surrogates of outcome in PBC in a real‐world setting.